Self-Directed Learning in Higher Education in Sri Lanka: Challenges in Implementing Policy - Bandara, Kapila (National Education Research and Evaluation Centre, 2022)
Human beings are entering into a strange new world in which rapid change will be the only stable characteristic. In this context, self-directed learning (SDL) is recognized as a desirable goal in tertiary education as it is found to comply with learner-centered approaches and enables students to navigate the change and minimize the risks they face. Sri Lanka has also realized this need to introduce SDL to the university system and several policy initiatives have been taken in this regard. the main objectives of this paper are to examine the policy initiatives introduced and identify the feasibility and the challenges in implementing them. For this purpose, data were collected using a mixed mode design. Findings revealed that several policy initiatives have been taken to promote SDL among the undergraduates in the Sri Lankan universities. The majority of the undergraduates have positive attitudes toward SDL, and they showed willingness to be self-directed learners. However, the majority of the academics were skeptical about SDL due to the challenges they foresee. Examination-oriented educational methods, ineffective assessment techniques, excessive numbers of students enrolled in courses, inadequacy of time and traditional practices of the lecturers are identified as obstacles to develop SDL in the Sri Lankan universities.
Keywords: Self-directed learning; Teacher-directed learning; Undergraduate education